KOMITMEN ORGANISASI MERUPAKAN VARIABEL INTERVENING PENGARUH ANTARA KEPUASAN KERJA TERHADAP KINERJA PEGAWAI (Studi Empirik di RSUD Sukoharjo) - HANDAYANI, DWI LUSI; HARIYANTI, Ibu (STIE Totalwin Semarang, 2011)
In the effort to increase the performance and prosperity of hospital employees, the organization needs to manage the job satisfaction, commitment of organization norms. Target of this research, was to test the effect of job satisfaction and organizational commitment in employees performance on BRSUD Sukoharjo. This sampleÂ research used purposive sampling technique and the data collected by questionare. The hypothesis tested by simple regression analysis and double regression with t test, f test and coefficient of determination. Result of research found that there are positive and significant influence between satisfaction of job, organizational commitment, toword the employees performance of BRSUD sukoharjo employees, either through partial and simultan. Based on that results, we suggest the way to increase performance in the future, management must employees performance itâs performance. Beside that, the hospitalâs management have to evaluate and implement activities Â duringÂ the periodically for better employees performance Â with organizational commitment, andÂ job satisfaction.